2016
DOI: 10.1186/s12860-016-0094-8
|View full text |Cite
|
Sign up to set email alerts
|

Connexin and pannexin channels in cancer

Abstract: Communication among cells via direct cell-cell contact by connexin gap junctions, or between cell and extracellular environment via pannexin channels or connexin hemichannels, is a key factor in cell function and tissue homeostasis. Upon malignant transformation in different cancer types, the dysregulation of these connexin and pannexin channels and their effect in cellular communication, can either enhance or suppress tumorigenesis and metastasis. In this review, we will highlight the latest reports on the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 191 publications
(234 reference statements)
1
60
0
Order By: Relevance
“…In addition, the possible involvement of pannexin channels also cannot be ignored (Panchin et al, 2000). Multiple studies suggest that these two types of hemichannels have a close relationship and work coordinately in the CNS that differentially regulates the ionic and metabolic fluxes and cellular function (Decrock et al, 2015; Jiang and Penuela, 2016). …”
Section: Connexin Hemichannelsmentioning
confidence: 99%
“…In addition, the possible involvement of pannexin channels also cannot be ignored (Panchin et al, 2000). Multiple studies suggest that these two types of hemichannels have a close relationship and work coordinately in the CNS that differentially regulates the ionic and metabolic fluxes and cellular function (Decrock et al, 2015; Jiang and Penuela, 2016). …”
Section: Connexin Hemichannelsmentioning
confidence: 99%
“…Concerning a possible use of CBX in cancer, it has been shown that CBX inhibits the expression of the apoptosis-inhibitor-protein BIRC5/survivin and thereby triggers apoptosis in K562 leukemic cells [46] and enhances TRAIL-induced apoptosis in human glioma [47]. Regarding its function as a gap junction inhibitor, particularly as a [48].…”
Section: Discussionmentioning
confidence: 99%
“…Transmembrane proteins, form channels for the release of ATP and other metabolites [210]. Auto-and paracrine cell-cell communication…”
Section: Cell-to-cell Communicationmentioning
confidence: 99%